Organization and administration of foreign student services in institutions of higher learning in Metropolitan Manila - Nuval, Beulah Dalao 1936- (1978)
This is a study on the state of foreign student services during the second semester, AY 1975-76 in twenty five institutions of higher learning in the Metropolitan Manila Area which were authorized by the Commission on Immigration and Deportation to admit foreign students and which had at least ten foreign students enrolled at the time of the survey. The methodology involved: the identification of all schools in Metro Manila which offer at least 4 year degree course and admitted at least 10 foreign students at the time of the study; the construction and administration of questionnaires and a checklist; and conducting of personal interviews. The major problems were found to be related to admission, visa/passport, study permit, language, socialization, orientation, physical/medical examination, health, emotion, vocation, vacation, housing, board and lodging, finances, meeting at airport, and academic matters. The major and minor problems are numerous and complex, and remarkably similar from campus to campus in Metro Manila, the United States and perhaps all over the world.
Mimeographed.
Thesis (D.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Students, Foreign -- Philippines -- Manila Metropolitan area; Personnel service in higher education -- Philippines